1993
DOI: 10.1159/000187475
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glomerular Hyperfiltration and Nephromegaly in Normo- and Microalbuminuric Type 2 Diabetic Patients

Abstract: Glomerular hyperfiltration, correlated with nephromegaly, is a frequent finding in type 1 (insulin-dependent) diabetes. In type 2 (non-insulin-dependent) diabetes, very few studies have been performed, and the results have been inconclusive. Glomerular filtration rate (GFR) and kidney volume, using 99mTc-DTPA scintigraphy and ultrasonography, respectively, were evaluated in 58 control subjects and 163 type 2 diabetic patients; 79 of whom were normoalbuminuric and 84 microalbuminuric. In the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…The reported prevalence of hyperfiltration varies widely from 6 to 75%, with high rates documented in new-onset diabetes and in certain ethnic populations [2,[7][8][9][10][11][12]22]. The high rates of hyperfiltration in new-onset diabetes may be explained, at least partly, by the acute metabolic effect of hyperglycaemia, as previous studies have demonstrated an association between hyperglycaemia and hyperfiltration as well as nephromegaly [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported prevalence of hyperfiltration varies widely from 6 to 75%, with high rates documented in new-onset diabetes and in certain ethnic populations [2,[7][8][9][10][11][12]22]. The high rates of hyperfiltration in new-onset diabetes may be explained, at least partly, by the acute metabolic effect of hyperglycaemia, as previous studies have demonstrated an association between hyperglycaemia and hyperfiltration as well as nephromegaly [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that systolic hypertension, reno-vascular disease, and increased arterial stiffness form a continuum with age in type 2 diabetes and these factors have been previously recognised to have a negative correlation with renal plasma flow [39,40] and with GFR [7,41]. Renal vascular resistance has been shown to be correlated with age in normal subjects [39] and blood flow to the renal cortex appears to be inversely related to renal vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of the prevalence of hyperfiltration in type 2 diabetes have varied from 0% [21,22], 6% [23] and 35% to 45% in recently diagnosed patients [12,24,25]. A prevalence of 62% was reported by Vedel [26].…”
Section: Hyperfiltration In Type 2 Diabetesmentioning
confidence: 99%